2015
DOI: 10.1007/s10528-015-9686-9
|View full text |Cite
|
Sign up to set email alerts
|

ALDH2*2 Allele is a Negative Risk Factor for Cerebral Infarction in Chinese Women

Abstract: Unlike its reported role in the cardiovascular diseases, little information is available for mitochondrial aldehyde dehydrogenase 2 (ALDH2) in the cerebrovascular function. We investigated the different effects of ALDH2 genotypes on the risk of cerebral infarction between the genders, because different genders had different smoking and/or dinking status which are also risk factors for cerebral infarction. 247 healthy Chinese Han people (controls, group 1), 287 Chinese Han male patients with cerebral infarction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Previous studies demonstrated that the frequency of ALDH2 G allele differed significantly among different races, even among different East Asian populations 38 , 39 . Previous studies showed that the ALDH2 genetic polymorphism plays an important role in several pathological conditions, including hepatitis, certain types of carcinomas, coronary artery disease, cerebral infarction 40 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that the frequency of ALDH2 G allele differed significantly among different races, even among different East Asian populations 38 , 39 . Previous studies showed that the ALDH2 genetic polymorphism plays an important role in several pathological conditions, including hepatitis, certain types of carcinomas, coronary artery disease, cerebral infarction 40 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Most importantly, ALDH2 is widely expressed in glial cells and neurons of the brain [10][11][12] while Alda-1 (N-(1,3-benzodioxol-5-ylmethyl)-2,6-dichlorobenzamid), a well-characterized ALDH2 agonist, have also been shown to provide efficacious neuroprotective effects against ischemic injury in the brain [41]. Furthermore, ALDH2*2 allele frequencies were found to be significantly lower among stroke patients in several epidemiological analyses [43,44]. About half of East Asia's populations are heterozygous for ALDH2, which represents a higher risk factor for stroke [45].…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in ALDH2 can influence the expression and function of this protein, and consequently increase susceptibility of the individual to a variety of diseases of the central nervous system (Hao et al, 2011;Yao et al, 2011;Li et al, 2015). In a study conducted by Li et al (2015), which included 369 Chinese patients with cerebral infarction and 247 healthy Chinese subjects, it was shown that the A allele in ALDH2 may be a significant risk factor for cerebral infarction in Chinese females .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Li et al (2015), which included 369 Chinese patients with cerebral infarction and 247 healthy Chinese subjects, it was shown that the A allele in ALDH2 may be a significant risk factor for cerebral infarction in Chinese females . Notably, Yao et al (2011) stated that the A allele in ALDH2 is an independent protective variable for patients who have had stroke and have a history of heavy alcohol consumption.…”
Section: Discussionmentioning
confidence: 99%